Supercontinuum generation in photonic crystal fiber using femtosecond pulses - Harun, Sulaiman Wadi; Akbari, Reza; Arof, Hamzah; Ahmad, Harith (IOP Publishing, 2011)
Supercontinuum (SC) generation in photonic crystal fiber (PCF) is demonstrated using an amplified femtosecond stretched pulses. The stretched pulse is obtained from a mode-locked Erbium-doped fiber laser and operates at 1564 nm with a repetition rate of 8.27 MHz and a pulse width of 340 fs. Using a 50 m long PCF, broad SC spectra are observed starting from 1220 and 1050 nm for the corresponding 5.1 and 177 kW pump and spanning a wavelength region of more than 1750 nm. At a maximum peak pump power of 177 kW, flat SC which extends over bandwidths of 660 and 486 nm are obtained using 50 and 100 m piece of PCF respectively. However, the output power level is higher for the 100 m PCF especially at longer wavelength region.